Determining the concentrations of radon and the rate of annual effective dose in some types of drinking water available in the Iraqi markets - Al-Hamidawi, Ali A. (Iraqi Journal of Physics, 2019)
In this research, radon concentrations in some types of healthy drinking water samples available in Iraq’s market were measured using a technique called Durridge RAD-7-H2O with closed loop. Then the rate of annual effective dose in human taken this water is determined. It was found that, radon concentrations in studied samples ranged between 1.2 Bq.m-3 to 142 Bq.m-3. The results of the radon concentrations and the rate of annual effective dose for drinking water samples were significantly lower than the USEPA and WHO recommended limits that equal 500 Bq/m3 and 1 mSv/y respectively.